2022
DOI: 10.3389/fspor.2022.902276
|View full text |Cite
|
Sign up to set email alerts
|

Greater Breast Support Is Associated With Reduced Oxygen Consumption and Greater Running Economy During a Treadmill Running Task

Abstract: IntroductionBreast pain is a major barrier to running for women. While breast support through the use of sports bras reduces breast-related discomfort, the effect of breast support on running performance is less understood. Therefore, the purpose of the current study was to evaluate the effect of greater breast support on oxygen consumption and running economy during a treadmill running task.MethodsFifteen female recreational runners performed a 10-min treadmill running task at their preferred running speed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…While Fong and Powell reported changes in running bioenergetics, running biomechanics were not reported (15). Several biomechanical factors were suggested to underlie the observed improvements in running performance including altered transverse plane trunk and pelvis kinematics and increased lower extremity stiffness (15). Evidence has demonstrated that increasing levels of breast support are associated with greater peak trunk and pelvis rotation angles as well as greater trunk and pelvis ranges of motion (9), supporting the assertions by Fong and Powell.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…While Fong and Powell reported changes in running bioenergetics, running biomechanics were not reported (15). Several biomechanical factors were suggested to underlie the observed improvements in running performance including altered transverse plane trunk and pelvis kinematics and increased lower extremity stiffness (15). Evidence has demonstrated that increasing levels of breast support are associated with greater peak trunk and pelvis rotation angles as well as greater trunk and pelvis ranges of motion (9), supporting the assertions by Fong and Powell.…”
Section: Introductionmentioning
confidence: 84%
“…As previous research (15) has demonstrated that breast size influences the effect of sports bra support on running performance, a repeated measures analysis of covariance (ANCOVA) was used to evaluate the effect of breast support on running cadence, stride length and contact time, as well as knee joint biomechanics while accounting for the influence of breast size on dependent variables. In the presence of a significant main effect of breast support, posthoc dependent samples t-tests were used to compare mean values between breast support conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations